Les critères de répartition des normes entre la loi et le règlement - Alarie, Jean; Boisvert, Guy (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1980)
Various groups and institutions are concerned about the proliferation of regulations. There is fear of an overflow into the regulatory field of standards that belong to the legislative domain. It therefore seems appropriate to draw up criteria for assigning standards to the respective areas of statutes and regulations. The logic for apportioning standards might be based on the principle that the placing of a standard in the hierarchy of unilateral normative instruments is directly related to the scope of its object and inversely related to its degree of intervention in the activity subjected to it. Before deciding to put a standard into a statute or to provide that it be enacted later under regulation-making authority, it is advisable to assess its degree of generality in relation to the concepts that surround it in the legislative draft, and also to measure its degree of materiality, i.e. the extent to which it embodies Government intervention in the activity that it is proposed to regulate. From a practical standpoint, however, the impact of the political environment on legislative drafting must not be ignored. Allowing for the influence of policy and politics on the design of the statute-regulations complex, three contiguous but distinct normative areas may be identified: standards that must belong to the domain of statutes ; standards that may be apportioned to either the domain of statutes or that of regulations ; and standards that would normally belong to the domain of regulations. The model suggested is not absolute and is liable to be modified by space and time considerations ; however, reference to it might help to rationalize the delegation of regulation-making authority.